Peningkatan Keterampilan Berbicara Melalui Permainan Karamba Kartu Gambar Cerita - Suci Rahayu; Ngatmini Ngatmini (STIKes Ibnu Sina Ajibarang, 2024)
The purpose of this study is to improve students' speaking skills in Indonesian language subjects by applying story picture card games (karamba) to fifth grade students of SD Negeri Purwosari 1, Sayung sub-district, Demak district. This type of research is a class action research which was conducted in two cycles. Each cycle consists of planning, action, observation, and reflection stages. The subject of this research was the fifth grade students of SD Negeri Purwosari 1, totaling 30 students. The object of this research is students' speaking skills. Data collection in this study was done by observation method. The data were analyzed using descriptive statistical analysis technique. The results showed that in cycle I, the average score of speaking skills obtained was 76.41 and the average percentage obtained was 75.68%, which was in the low category. In cycle II, the average speaking skill score obtained was 82 and the average percentage obtained was 90.64% in the high category. The percentage increase from cycle I to cycle II was 14.21%. This shows that there has been an increase in the percentage of speaking skills of fifth grade students of SD Negeri Purwosari 1. Based on the results of the study, it can be concluded that the application of karamba games (story picture cards) can improve students' speaking skills in Indonesian language subjects in grade V SD Negeri Purwosari 1, Sayung sub-district, Demak district in the 2023/2024 academic year.